2023
DOI: 10.3390/jcm12093342
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lung Ultrasound in the Follow-Up of Children with Previous SARS-CoV-2 Infection: A Case-Control Assessment of Children with Long COVID or Fully Recovered

Abstract: Lung ultrasound (LUS) can detect lower respiratory tract involvement in children with acute SARS-CoV-2 infection. However, its role in follow-up assessments is still unclear. To describe LUS findings in children after SARS-CoV-2 infection, we conducted a prospective study in a population of pediatric patients referred to the post-COVID unit in a tertiary center during the study period from February 2021 to May 2022. Children were classified as recovered from acute infection or with persisting symptoms. LUS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…According to our findings, in a prospective study including 647 children aged 8 years, Buonsenso et al 45 observed persistent symptoms in about 40% of patients 2 months after acute infection.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…According to our findings, in a prospective study including 647 children aged 8 years, Buonsenso et al 45 observed persistent symptoms in about 40% of patients 2 months after acute infection.…”
Section: Resultssupporting
confidence: 70%
“…The usefulness of LUS in detecting lower respiratory tract involvement in children with SARS-CoV-2 acute infection is well known. 45 In an observational study including eight children during acute COVID-19, Denina et al 46 firstly demonstrated a concordance of LUS findings with radiologic findings in seven out of eight patients, suggesting that LUS may be a reliable method to detect lung abnormalities in children with COVID-19. However, the role of LUS in follow-up assessment is still unclear.…”
Section: Resultsmentioning
confidence: 96%
“…Almost all children displayed either a normal LUS pattern or minimal artifacts, signifying complete lung recovery post initial infection. Importantly, the LUS findings were similar in both the recovered children and those who developed long COVID [61].…”
Section: Discussionmentioning
confidence: 63%
“…Nonspecific abnormalities, such as the presence of multiple bilateral B-lines, indicating a reduction in air content, thickening of the pleural line with associated abnormalities, and peripheral consolidation, may be observed on the LUS scans of children with COVID-19 pneumonia [56]. Since the early stages of the pandemic, LUS has demonstrated to be a helpful tool to assess lung conditions, monitor any changes over time, and guide therapeutic decisions in both adults and children [57][58][59][60][61]. The LUS in this study was conducted using a linear probe.…”
Section: Cmentioning
confidence: 99%